PENYELESAIAN PERKARA TINDAK PIDANA KEKERASAN FISIK YANG DILAKUKAN SECARA BERSAMA-BERSAMA MELALUI ASAS KEADILAN RESTORATIF (RESTORATIVE JUSTICE) DI TINGKAT KEPOLISIAN RESORT SUMENEP - Amir, Tolak; Fithry, Abshoril (2024)
Restorative Justice is a mechanism for resolving criminal acts by involving perpetrators, victims, families and other related parties. Procedures for resolving criminal acts through the principles of restorative justice at the police level are contained in Police Regulation (Perpol) no 8 of 2021 which has provided qualifications for several requirements and procedures for handling criminal acts based on restorative justice consisting of general and specific requirements with several more detailed requirements consisting of material and formal requirements. In the context of resolving the criminal act of beatings at the Sumenep resort police, where the beating was carried out by a suspected 6 (six) people against the victim Sukki, a resident of Lapa Laok Village, Pasongsongan District, Sumenep Regency, it was deemed formally and materially flawed because the crime of beating up accompanied by kidnapping of the victim This is quite a serious action because it really threatens the victim's life, therefore, the Sumenep Resort Police should continue the case of the criminal act of beating. This research method uses normative research. This writing explains that the formal and material requirements regulated in Article 5 in conjunction with Article 6 of Police Regulation No. 8 of 2021 experience legal ambiguity because minimum standards are not explicitly regulated regarding criminal threats and fines so that the case can be or not to be resolved through the principles of restorative justice and there is disharmony with Article 5 of Prosecutor's Regulation No. 15 of 2020 concerning Termination of Prosecution Based on Restorative Justice which explicitly emphasizes criminal acts that carry a penalty of no more than 5 (five) years and the loss suffered by the victim is no more from Rp. 2,500,000.00 (two million five hundred thousand rupiah). Then the case can be set aside or closed by law.